Emergence: Towards a Historiography of Canadian Defence Research during the Second World War - Ridler, Jason (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2008)
The Second World War forced Canada to become a nation with effective defence research assets, and these assets were among the nation's many contributions to victory in 1945. The historical literature on these developments has been slow to develop though it is now becoming an increasingly popular field of study. This premier historiography attempts to chart how and why the writings on Canada's defence research efforts during the Second World War have grown, its various forms of discourse, and its major themes, controversies, and deficiencies.